Development of cost effective soya extended whey incorporated chicken meat nuggets. Issue 3 (11th May 2015) - Singh, Veer Pal; Pathak, Vikas; Nayak, Narendra Kumar; Bharti, Sanjay Kumar
Abstract : Purpose: – This purpose of this paper was to conduct a study with an aim to reduce the cost of chicken nuggets by replacing part of lean meat with soy flakes. The suitability of chilled paneer whey was also assessed in place of ice water. Design/methodology/approach: – In the development of chicken nuggets, water-soaked soya flakes at the rate of 20 per cent were used in the formulation. The chilled whey at the rate of 8 per cent of the formulation was used to prevent the rise of temperature during emulsion preparation. Findings: – The product prepared in this way gave 5 per cent more yield than normal preparation in which ice water was used. The protein content in the preparation had gone significantly ( p < 0.05) higher and moisture significantly ( p < 0.05) lower than the normal control. The other proximate composition of chicken nuggets like fat and ash revealed no significant ( p > 0.05) change in the product. Initially, thiobarbituric acid value and pH were observed lower in soya flakes-extended nuggets than the control. The overall acceptability was higher, that might be due to good binding and proper emulsion preparations. Research limitations/implications: – Some experiments on amino acid profile and fatty acid profile are also required for further know-how about the actual nutritional status of chicken meat nuggets. Practical implications: – The products will be of immense value for the nutritional supplement and utilization of by-products like whey. It may also be a cost-effective formulation. Social implications: – The products will be acceptable to all commodities because it is made up of chicken meat. Originality/value: – The cost of the formulation was also lower than the chicken nuggets used without soya flakes and whey because cost of meat was greater than the soya. The whey produced in paneer production costs less or by-product rich in protein materials can be better utilized into valuable products. The developed product seems to have great applications in the food industry and acceptability among consumers.